2016
DOI: 10.11005/jbm.2016.23.3.175
|View full text |Cite
|
Sign up to set email alerts
|

Proximal Femoral Geometry as Fracture Risk Factor in Female Patients with Osteoporotic Hip Fracture

Abstract: BackgroundProximal femoral geometry may be a risk factor of osteoporotic hip fractures. However, there existed great differences among studies depending on race, sex and age of subjects. The purpose of the present study is to analyze proximal femoral geometry and bone mineral density (BMD) in the osteoporotic hip fracture patients. Furthermore, we investigated proximal femoral geometric parameters affecting fractures, and whether the geometric parameters could be an independent risk factor of fractures regardl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 38 publications
3
23
2
Order By: Relevance
“…Based on anatomical form and location, hip fractures can be classified into cervical and trochanteric fractures. In recent decades, several studies have indicated that women with trochanteric fractures are older, thinner, shorter, and have less bone mass at the proximal femur. In the current study, we found that the average age of patients with trochanteric fractures was approximately 4 years older than that of patients with cervical fractures, and in female patients, those with trochanteric fractures were approximately 5 years older.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Based on anatomical form and location, hip fractures can be classified into cervical and trochanteric fractures. In recent decades, several studies have indicated that women with trochanteric fractures are older, thinner, shorter, and have less bone mass at the proximal femur. In the current study, we found that the average age of patients with trochanteric fractures was approximately 4 years older than that of patients with cervical fractures, and in female patients, those with trochanteric fractures were approximately 5 years older.…”
Section: Discussionsupporting
confidence: 54%
“…The OR for fractures decreased when the cross‐sectional area (CSA) and neck length of the femur increased 1.97 times and 1.73 times in femoral neck fractures, respectively, and the OR for fractures increased when the femoral neck width increased 1.53‐fold. In addition, the OR for fractures increased when the femoral neck width increased 1.45‐fold in trochanteric fractures. However, Li et al .…”
Section: Introductionmentioning
confidence: 92%
“…Owing to the high rate of morbidity and mortality in hip fractures, it is necessary to predict the occurrence of hip fractures accurately. Various studies have demonstrated that the proximal femur geometry was associated with the occurrence of hip fractures in elderly patients [12,18]. Similar to previous studies [10,13], a larger neck shaft angle and a longer femoral neck length were found to be independent predictors for hip fractures in both sexes.…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, several studies revealed that the simple measurement of the proximal femur geometry could predict the occurrence of hip fractures independently of BMD [9,10]. At present, the proximal femur geometry had been extensively investigated to predict the occurrence of hip fractures in elderly patients [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Intertrochanteric fractures account for nearly half of all hip fractures. Coinciding with the aging of the population, the incidence of osteoporosis in the elderly has increased, and the incidence of intertrochanteric fractures has increased year by year. The treatment of intertrochanteric fractures of the femur can be divided into conservative treatment and surgical treatment.…”
Section: Introductionmentioning
confidence: 99%